Satysfakcja pracownicza w zmieniającym się przedsiębiorstwie - Pietroń-Pyszczek, Agata (Employee's satisfaction in changing enterprise, 2006)
The paper is attempt of answering on question, how circumstances changes of functioning present firms can influence on attitudes and level of employee's satisfaction. In this seizure the problems of formation of workers' satisfaction in virtual enterprises were introduced. It was also established, that endeavor of companies to height of employment flexibility - for example across preferring temporary employment, short employment contracts, part-time works - can lower level of workers' satisfaction.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 647-650